Evaluation of the impact and evolution of community health agents in early breast cancer detection in the Itaberaí Project (Goiás) - Costa, Christina Souto Cavalcante; Rodrigues, Danielle Cristina Netto; Correia, Rosangela da Silveira; Junior, Ruffo Freitas-; Watanabe, Priscila Dias; Novato, Luana Marques; Nascimento, Nicaella Eterna de Oliveira Santos (Mastology, 2026)
Objective: This study aimed to assess the impact and evolution of the participation of Community Health Agents (CHAs) in the early detection of breast cancer in the Itaberaí Project, Goiás, through their adherence and performance. Methods: The methodology was based on structured training for CHAs, including educational activities, practical simulations, and constant supervision, ensuring greater confidence in performing the examination and improving communication skills. This strategy has contributed to enhancing patient care flow, strengthening professional confidence, and promoting more humanized and effective healthcare. Results: The outcomes indicated a positive impact, with improved disease identification and increased access for women to appropriate healthcare. In 2022, initial resistance was observed among some professionals (24; 54.1%) due to insecurity in performing the breast physical examination and lack of knowledge about the benefits of the initiative. However, with continuous training, adherence significantly increased (9; 21.4%). Statistical analyses using the chi-square test demonstrated a significant difference between initial resistance and adherence after training (χ²=14.86; p=0.0001). Between 2024–2025, most CHAs were more committed and aware of the importance of their role in prevention. The first cycle of the project (2022–2024) was structured into three stages, allowing for gradual improvement in the strategy. Initially, the project included eight Basic Health Units (UBSs), expanding to ten, with the participation of 76 CHAs, divided into a control group (34; 44.7%) and an intervention group (42; 55.3%). In the intervention group, six (14.3%) male CHAs did not perform the examination, and two (4.8%) female CHAs chose not to, with one (2.4%) later adhering after training and professional support. Conclusion: The growing adherence of CHAs reinforces the importance of training and confirms the effectiveness of the initiative, establishing the Itaberaí Project as a model for primary care, prevention, and community healthcare, highlighting its positive impact on public health.